Assessing the impacts of infectious disease on reproductive success in New Zealand sea lions (Phocarctos hookeri) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Veterinary Science in Wildlife Health at Massey University, Palmerston North, Manawatū, New Zealand - Michael, Sarah Anne (Massey University, 2014)
Poor reproductive success is one factor that may be perpetuating the population decline of the threatened New Zealand (NZ) sea lion (Phocarctos hookeri). The species has a severely restricted distribution, with 99% of breeding occurring on the remote NZ sub-Antarctic islands and amongst the lowest expected reproductive outputs compared to other otariids. Infectious disease, particularly septicaemia caused by the bacterium Klebsiella pneumoniae is known to be a major mediator of early pup mortality, but the role of infectious disease in impairment of reproductive success has not been investigated. This thesis aimed to fill this knowledge gap by investigating three areas of concern. Firstly, the role of infectious disease in stillbirth of NZ sea lion pups was examined with a histopathological study of archived necropsy tissues. Secondly, the seroprevalence of adult and juvenile NZ sea lions to Toxoplasma gondii, a known cause of reproductive failure, at several locations was evaluated. Finally, a survival analysis was conducted to model the long term survival and reproductive success of pups that were treated with ivermectin as pups, to assess ongoing benefits of early hookworm burden removal. In contrast to the mass mortalities seen with bacterial disease in NZ sea lion colonies, at least in the topics covered in this thesis, the role of infectious disease contributing to poor reproductive success is apparently minimal. No specific infectious agents were identified to have caused the death of the stillborn pups examined, however pneumonia was diagnosed in four animals. A low seroprevalence to T. gondii was found in mainland but not sub-Antarctic colonies, however those animals with strongly positive titres showed no clinical signs and had reproduced normally. Finally, although the survival analysis was limited by small sample size and very poor juvenile survival, it depicted promising trends for improved survival for those pups treated with ivermectin as pups. All studies have generated areas for future research and recommendations for further conservation management of this vulnerable species.
Keywords: Hooker's sea lion; New Zealand sea lion; Phocarctos hookeri; Reproduction; Disease; Conservation; New Zealand